High power, extended temperature range, and overcharge-resistant rechargeable battery cells and battery packs
By using high-conductivity aluminum current collector and specific positive electrode materials in lithium-ion batteries, the safety and performance problems of lithium-ion batteries in mechanical misuse, low temperature and long-term storage are solved, and the stability of fast charging and discharge and high power transmission is achieved.
Patent Information
- Application Number
- JP2021560078
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-12
- Filing Date
- 2020-04-10
- Publication Date
- 2025-02-10
- Estimated Expiration
- 2040-04-10
AI Technical Summary
Existing lithium-ion batteries have safety hazards in mechanical misuse, low temperature environment and long-term storage processes, and cannot be charged and discharged quickly, and their performance is limited.
The lithium-ion battery design is adopted that contains a high-conductivity aluminum current collector, using a negative electrode material with a redox potential of more than 400mV and a non-uniform distribution of cobalt aluminum cobalt oxide positive electrode material, combined with a high ion conductive separator and specific electrolyte to achieve high power transmission of the battery and stability in extreme environments.
It realizes the safety and high performance of lithium-ion batteries under extreme mechanical misuse, low temperature and long-term storage conditions, supports fast charging and discharge, and avoids the risk of lithium metal precipitation and internal short circuit.
Smart Images

Figure 0007628503000002 
Figure 0007628503000003 
Figure 0007628503000004
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application is a continuation-in-part of U.S. Patent Application No. 16 / 383,079, filed April 12, 2019. This application follows and claims the benefit of International Application No. PCT / US2019 / 027284, filed April 12, 2019. The entire contents of each of these U.S. and international applications are incorporated herein by reference. [Technical field]
[0002] The present disclosure relates to lithium-ion secondary batteries and uses thereof. [Background technology]
[0003] Lithium-ion batteries are the primary power source for many portable electronic devices for a variety of reasons. These reasons include the high energy density, high specific energy, and long cycle life associated with the technology. However, commercially available lithium-ion cells present safety concerns, especially when they are mechanically abused. Lithium-ion cells cannot be charged quickly or at very low temperatures, and generally perform poorly at low temperatures. Lithium-ion cells can present significant safety hazards, especially when subjected to mechanical abuse that causes them to develop internal short circuits. Lithium-ion cells are susceptible to overcharging and overdischarging, which can result in undesirable performance loss and potentially dangerous events if a battery or battery cells are overcharged or overdischarged.
[0004] Long-term storage or transportation of lithium-ion batteries is problematic because lithium-ion batteries are susceptible to over-discharge. Due to the limited rate of self-discharge, long-term storage of a battery pack results in the battery pack voltage slowly approaching 0V. In a discharged battery pack having many cells, inherent or induced cell-to-cell capacity imbalances can cause a subset of the cells to go into voltage reversal or over-discharge. In most common lithium-ion battery cell designs, these voltage conditions can initiate and promote deleterious reactions that irreparably impair cell performance.
[0005] Without wishing to be bound by theory, it is understood that the susceptibility of current lithium-ion batteries to overdischarge is due to the use of a combination of graphite anode material and copper current collector material. Copper is used because it is less susceptible to electrochemical alloying with lithium at the redox potential of graphite and has high electrical conductivity. However, copper is used because the anode is at high potential (vs. Li / Li + The copper oxide can be oxidized when the potential is increased to 0.5 V (~3 V at 1000 mAh). Such high potentials can occur if the cell is overdischarged. It is understood that the copper oxide redeposits in fibrous form. This redeposition can limit the lifetime and lead to potential internal short circuits if the cell is subsequently recharged. Furthermore, passivation films formed at the interfaces of the electrolyte and electrode materials that mitigate parasitic decomposition reactions can be decomposed under oxidative overdischarge conditions, especially at elevated temperatures. When the cell is cycled again, these passivation films inevitably reform, consuming more lithium and reducing the total capacity of the cell.
[0006] One approach to increase the overdischarge stability of graphite anodes is to replace the copper current collector material with stainless steel or titanium, which are more resistant to dissolution at high potentials. However, both stainless steel and titanium have higher electronic resistivity than copper. This high electronic resistivity requires cell designs with thicker current collectors, which ultimately limits the power performance of the cell. Another approach to improve the overdischarge stability of graphite anodes is to pre-lithiate the anode, which reduces the anode potential at overdischarge conditions below the copper dissolution potential. However, this approach may result in a lower cathode potential at overdischarge corresponding to excessive lithiation that may cause decomposition, which may also lead to an increased risk of Li plating on the anode at full charge.
[0007] To avoid these and other safety issues, cells in currently available lithium-ion batteries are electronically monitored and their state-of-charge controlled. These tasks may be performed using a battery management circuit (BMC). In addition to avoiding deep-discharge of lithium-ion cells to avoid decomposition mechanisms such as copper dissolution, the battery management circuit may also provide protection from overcharging. The cell monitoring and state-of-charge control used in current lithium-ion batteries often exceeds that used in other rechargeable battery technologies, such as lead-acid or nickel-metal hydride batteries, where battery management circuitry may be omitted in many applications.
[0008] Cells made with graphite anodes are most often designed with an anode / cathode capacity ratio "n / p" greater than 1 to avoid lithium plating on the anode during charging. Because the graphite intercalation potential is only ~0.1V higher than the lithium metal plating potential, lithium metal deposition can occur during typical modes of battery charging as opposed to the favorable intercalation of lithium into the graphite in the anode. This deposition reaction poses a safety risk and can cause catastrophic cell failure. A common precaution to protect against Li metal plating is to design the cell with n / p>1 (typically between 1.1 and 1.3). This ensures that the lithium reserve in the cell is less than the capacity dictated by the number of intercalation sites in the graphite anode crystal structure. In this cell configuration, a fully charged state is defined as a fully deintercalated cathode and a partially intercalated anode. Such cell designs require careful monitoring by the BMC to avoid an upper voltage threshold associated with accelerated cathode decomposition. On the other hand, if the cell is designed with n / p<1, as the cell voltage increases during charging, there exists a point at which the lithium metal plating reaction becomes the thermodynamically favored electrochemical reaction at the anode after all graphite intercalation sites are filled with Li. Such cell designs require careful monitoring by the BMC to avoid an upper voltage threshold at which Li plating would occur. This predicts that at n / p ratios less than 1, the risk of Li plating leading to catastrophic failure becomes too great.
[0009] Cells made with graphite anodes do not charge well at low temperatures. Due to increased cell polarization due to low charge rates at low operating temperatures, the anode potential can easily fall below the lithium plating potential, but only by 0.1 V, accelerating cell degradation and even catastrophic failure. Thus, cells made with such designs have severe limitations on their charging power capability at low temperatures. Low temperature charging may not be possible at all without the use of an external heating device, and careful monitoring by the BMC is required to avoid high rate charging at low temperatures.
[0010] During storage and operation of Li-ion cells, parasitic interactions between cell components can lead to gassing, resulting in increased pressure and reduced battery performance. Gassing is exacerbated at elevated temperatures and often when cells are subjected to electrolyte oxidation potentials. In both prismatic and pouched configurations, gas buildup within the cells can lead to mechanical distortion of the battery pack case and can compromise the connections between cells within the battery pack, thus increasing the risk of catastrophic failure. Furthermore, excessive pressure can rupture individual cell seals, resulting in the release of toxic gases and premature cell failure.
[0011] Currently, lead (Pb-acid) batteries are used in vehicle ignition and start-stop battery applications, e.g., "starting-lighting-ignition" (SLI) applications, because robust cells are required to transfer power over a wide range of temperatures. However, as vehicles become increasingly hybridized, additional energy consuming components (i.e., air conditioning, regenerative braking, seat warmers) are being powered by Pb-acid batteries. This is pushing Pb-acid batteries out of their ideal operating window as higher states of charge (SOC) are accessed and more cycles are performed. As a result, Pb-acid batteries are reduced in performance and replaced more frequently.
[0012] Thus, there remains a need for a battery technology that provides some of the desirable characteristics of lithium-ion batteries, such as long cycle life, and the characteristics currently offered by lead-acid SLI batteries, such as high power, fast recharge, and low temperature performance. Additionally, technology that provides improved safety, including the ability to safely withstand extreme mechanical abuse and operate safely down to 0 V, without external circuitry for protection from deep discharge, is highly desirable. Summary of the Invention
[0013] The following summary is provided to facilitate understanding of some of the innovative features unique to the present disclosure and is not intended to be a complete description, A complete understanding of the various aspects of the present disclosure can be obtained by taking the entire specification, claims, drawings, and abstract as a whole.
[0014] Disclosed are rechargeable lithium-ion cells and packs that are robust and extremely safe, provide high power delivery and acceptance capabilities, have long cycle life and excellent performance at high and low temperatures, are highly resistant to mechanical abuse, and have long storage life.
[0015] It has been found that the electrochemical cells of the present disclosure are surprisingly resistant to extreme mechanical abuse and continue to function as electrochemical cells, i.e., maintain charge and discharge even after such mechanical abuse. Cells of some embodiments provided herein can also be charged and discharged at extremely low temperatures, can be stored at zero volts for extended periods of time without damage, can withstand overcharging without damage to the cell, or combinations thereof.
[0016] The cells provided herein have the formula Li 1+x MO 2+yThe present invention includes a cathode made of an electrochemically active polycrystalline cathode material defined by or including the formula: where -0.9≦x≦0.3, -0.3≦y≦0.3, and M comprises 80 atomic percent or more of Ni relative to the totality of M. The electrochemically active cathode material is also characterized by a non-uniform distribution of Co on, within, or throughout the particles. The active cathode material enables improved rate capability and cell operating life compared to prior art Li-ion cathode materials. The active cathode material may be designed to reduce dissolution of transition metals, which is known to exacerbate parasitic decomposition and gassing reactions in the anode.
[0017] The cells provided herein have a Li / Li + The anode material includes electrochemically active materials defined by a redox potential greater than 400 mV at Li / Li + By operating at least 400 mV above the redox potential, the tendency of the cell to plate lithium during charging is greatly reduced, since the electrodes must be polarized by at least 400 mV to reach the thermodynamic potential for plating. The cells provided herein can achieve high power transfer even at low temperatures, since the polarization caused by the low rate of change at lower temperatures can be overcome without the risk of lithium plating. Li / Li + Cells containing anodes with redox potentials close to that of the anode cannot tolerate large polarizations due to low charge rates because these polarizations are believed to result in lithium plating onto the anode.
[0018] The cells may be of any configuration such as cylindrical or pouch cells.
[0019] The anode and cathode are in ionic contact with and separated by a separator. The separator may include or be a polymeric separator. In some embodiments, the separator may include a polyolefin. In some embodiments, the separator may further include a ceramic coated on one or more of the separator surfaces or embedded within the polymer (optionally on one or more of the separator surfaces). The ceramic may be a ceramic, such as a ceramic oxide. In some embodiments, the separator is or includes aluminum oxide.
[0020] The cells of the present disclosure have the ability to be configured in an anode-dominated manner, such that the area ratio of the anode to the cathode is optionally less than or equal to 1. Additionally or alternatively, the capacity ratio of the electrochemically active anode material to the electrochemically active cathode material is less than or equal to 1.
[0021] An electrolyte may be included, which may include a solvent and a salt. Optionally, the solvent is a carbonate solvent or a combination of one or more carbonate solvents and other suitable materials. The salt is optionally a lithium salt, optionally a LiPF6 salt in a mixture of propylene carbonate, ethyl methyl carbonate, and methyl butyrate.
[0022] The anode and cathode may include a binder mixed with the active anode and cathode materials, which is optionally a polymeric binder, optionally including or consisting of polyvinylidene fluoride (PVDF). [Brief description of the drawings]
[0023] The electrochemical cell according to the present disclosure will now be more fully described with reference to the accompanying drawings, in which various aspects are shown. However, the present invention may be embodied in many different forms and should not be construed as being limited to the aspects set forth herein. Rather, these aspects are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art. Like reference numerals refer to like elements throughout. These and other aspects, advantages, and features of the present disclosure will become more apparent by describing in more detail exemplary embodiments thereof with reference to the accompanying drawings, in which: [Figure 1] FIG. 1 is a schematic diagram of one embodiment of a lithium-ion cell, with the electrode stack detailed on the right. [Diagram 2] 1 illustrates capacity (Ampere-hours (Ah)) versus voltage (Volts (V)) at various rates of charge and discharge at room temperature for cells according to some embodiments provided herein. [Diagram 3] 1 illustrates capacity (Ampere-hours (Ah)) versus voltage (Volts (V)) at various rates of charge and discharge at −50° C. for cells according to some embodiments provided herein. [Figure 4] 1 illustrates cell discharge capacity (mAh) versus cycle number at 45° C. for two cells according to some embodiments provided herein at high rate cycling. [Diagram 5] 1 illustrates capacity (mAh) versus voltage (Volts (V)) for charging (A) and discharging (B) at various constant powers at room temperature for a cell according to some embodiments provided herein. [Figure 6] 1 illustrates cell voltage (Volts (V)) and electrode voltage (Volts (V)) vs. Li standard versus time (min) during voltage reversal at room temperature for a cell according to some embodiments provided herein. [Figure 7] 1 illustrates a graph of capacity (Ah) versus voltage (volts) for room temperature discharge of a cell according to some embodiments provided herein before and after the cell was polarized. [Figure 8]1 illustrates the discharge capacity (mAh) versus voltage (volts) for repeated high-rate pulse discharge at −18° C. of a cell according to some embodiments provided herein before and after the cell was polarized. [Figure 9] 1 illustrates cell voltage (Volts (V)) and electrode voltage (Volts (V)) vs. Li standard versus time (min) at room temperature for 10% overcharge of a cell according to some embodiments provided herein. [Figure 10] 1 illustrates a graph of capacity (Ah) versus voltage (volts) for discharge at room temperature for a cell according to some embodiments provided herein before and after the cell was overcharged. [Figure 11] 1 illustrates the discharge capacity (mAh) versus voltage (volts) for repeated high-rate pulse discharge at −18° C. of a cell according to some embodiments provided herein before and after the cell was overcharged. [Figure 12] FIG. 1 illustrates capacity (Ampere-hours (Ah)) versus voltage (Volts (V)) at various rates of charge and discharge at room temperature for a cell according to some embodiments provided herein before and after the cell was subjected to extended cycling and then stored under 0V conditions. [Figure 13] 1 illustrates voltage (Volts (V)) and temperature (° C.) versus time (seconds) during a blunt nail penetration abuse test for a cell according to certain embodiments provided herein. [Figure 14] FIG. 1 illustrates the capacity (Ampere-hours (Ah)) versus voltage (Volts (V)) of a cell according to some embodiments provided herein upon discharge at room temperature before and after the cell was subjected to a round bar crush test. [Figure 15] FIG. 1 illustrates a cell according to some embodiments provided herein that continues to function without defects after the cell is subjected to multiple extreme mechanical abuses. [Figure 16] FIG. 1 illustrates capacity (Ampere-hours (Ah)) versus voltage (Volts (V)) upon discharge at room temperature for a cell according to some embodiments provided herein before and after the cell was subjected to multiple extreme mechanical abuse. [Figure 17]1 illustrates the cell discharge capacity (Ah) versus cycle number for continuous cycling of a cell according to some embodiments provided herein after the cell was subjected to multiple extreme mechanical abuse. [Figure 18] FIG. 1 illustrates capacity (Amp-hours (Ah)) versus voltage (Volts (V)) upon discharge at room temperature for a cell according to some embodiments provided herein before and after the cell was subjected to multiple extreme mechanical abuse, 1000 cycles, and 33 months of storage at 0V. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Surprisingly, a positive electrode comprising an electrochemically active polycrystalline cathode material, optionally having a non-uniform distribution of cobalt, aluminum, or both, and a Li / Li + It has been found that the disclosed lithium-ion cells, comprising a negative electrode including an electrochemically active negative electrode material characterized by an electrochemical redox potential of 400 mV or more at 1000 V, coated on an aluminum current collector, can safely survive extreme mechanical abuse such as nail penetration and round bar crushing. Surprisingly, the disclosed cells continue to function electrochemically after such abuse without significant loss in performance. In addition, the disclosed cells have the unique ability to support extremely high charge rates, have excellent recovery after long-term storage in a deeply discharged state (e.g., 0 V), and can be charged at high rates (e.g., 1 C) at extremely low temperatures, such as below -40°C. Thus, the disclosed cells address many of the problems with other battery systems and technologies by providing an exceptionally robust and safe battery system that can be used in many types of cells, including pouch cells, and in many different applications.
[0025] As used herein, "absorption" may refer to an alloying reaction by intercalation or insertion or conversion of lithium into an active material. In this specification, absorption may be referred to as "lithiation."
[0026] As used herein, "desorption" may refer to a dealloying reaction by deintercalation or deinsertion or conversion of lithium into an active material. Desorption may be referred to herein as "delithiation."
[0027] As used herein, in the context of lithium-ion cells, "cathode" means the positive electrode and "anode" means the negative electrode.
[0028] As used herein, an "active material" is a material that participates in the electrochemical charge and discharge reactions of an electrochemical cell, such as by absorbing or desorbing lithium.
[0029] The lithium-ion cells disclosed herein may be safely discharged to 0V without affecting their performance. These lithium-ion cells may also safely withstand high degrees of overcharging and voltage reversal, the latter characteristic allowing batteries made from these cells connected in series to also be discharged to 0V without addressing the individual cells. Because the disclosed lithium-ion cells and batteries can be discharged to 0V, a number of advantages are provided. For example, the disclosed lithium-ion cells and batteries may be stored and / or shipped in a discharged state to provide improved safety. Due to the cells' high resistance to overcharging and overdischarging, batteries made therefrom may withstand losses or failures in battery management while maintaining performance and life at safe and useful levels. The lithium-ion cells provided herein may also be charged very quickly and at low temperatures without affecting their safety, performance, or life. This makes the present lithium-ion cells well suited for applications such as electric load leveling and start-stop vehicle batteries. Furthermore, such lithium-ion cells have excellent stability at high temperatures and excellent performance at very low temperatures.
[0030] Without being limited to one particular theory, it is believed that the anode structure and material selection greatly assist in providing some of the unique features of the electrochemical cell provided herein. One approach to provide a lithium-ion battery that can be discharged to 0V or stored in a discharged state while avoiding at least the decomposition of the commonly used copper current collector is to use metals such as titanium or stainless steel in the current collector, which are less susceptible to oxidation. However, titanium and stainless steel have lower electrical conductivity than copper. For example, the electrical conductivity of copper is more than 20 times higher than that of titanium. As a result, the rate performance of a cell using titanium or stainless steel instead of copper may be lower than that of copper. This makes the rate performance provided by cells employing titanium or stainless steel current collectors insufficient for some applications. Although the use of titanium or stainless steel current collectors is believed to provide improved overdischarge performance, the use of titanium or stainless steel is believed to make the cell unsuitable for applications where high power performance is desired.
[0031] As explained herein, the problem with other metals commonly used for current collectors is the low Li / Li ratio, such as aluminum. + At potentials of less than 0.5 V (e.g., vs. Li / Li + This is addressed by providing an electrochemical cell that includes a current collector for the negative electrode that includes or is made exclusively of a metal that has an electrochemical reactivity with lithium at a voltage of less than 0.1 V to 0.5 V at Li / Li. + The LTO may be used in conjunction with an electrochemically active negative electrode material defined by a redox potential of 400 mV or more at 10 ... + The electrochemical redox potential is 1.55 V at 1000 .mu.m, which is the potential at which aluminum alloys with lithium (vs. Li / Li +The electrochemical redox potential of the negative electrode material is higher than 0.4V at 100V (0.4V at 100V). Thus, when LTO (as an example) is used, which has an electrochemical redox potential of 1.55V vs. lithium, copper-related issues such as copper dissolution can be avoided by using aluminum as the negative electrode current collector. Furthermore, without wishing to be bound by theory, it is understood that a solid electrolyte layer (SEI), which is understood to include electrolyte reduction products, does not form on the electrochemically active negative electrode material used herein due to its high potential vs. lithium. These properties, combined with the ability to be safely discharged to 0V, result in an unintended improvement in the safety and stability of lithium-ion cells.
[0032] Furthermore, a negative electrode comprising an electrochemically active negative electrode material having an electrochemical redox potential of 400 mV versus lithium, with highly reversible Li intercalation at electrochemical change rates that are readily achievable, and a current collector comprising aluminum is relatively conductive, such that a lithium-ion cell comprising such a negative electrode can provide high rate capability and good life for both charging and discharging.
[0033] Thus, the electrochemical cells provided herein are + The negative electrode includes an electrochemically active negative electrode material having a redox potential of 400 mV or more at 1000° C. The electrochemically active negative electrode material is coated on an aluminum current collector. In some embodiments, the positive electrode also includes an electrochemically active polycrystalline cathode material coated on an aluminum current collector. The aluminum current collector is optionally in the form of a sheet of Al or an aluminum alloy, and may be in the form of a foil, a solid substrate, a porous substrate, a grid, a foam, or an Al-coated foam, or other shapes known in the art. In some embodiments, the aluminum current collector is a foil. The grid may optionally include expanded metal grids and perforated foil grids.
[0034] The positive electrode also includes a current collector. The current collector for the positive electrode may be made of aluminum, such as an aluminum alloy. The aluminum current collector may optionally have the shape of a sheet, foil, solid substrate, porous substrate, grid, foam, or Al-coated foam, or other shapes known in the art. In some embodiments, the aluminum current collector is a foil. The grid may optionally include expanded metal grids and perforated foil grids.
[0035] The current collector for the anode or cathode is optionally associated with a tab that can be used to electrically connect the cell to a circuit of use. Each of the anode and cathode current collectors may be electrically associated with a tab. The tab may be made of any suitable material, such as aluminum or other materials known in the art. The tab is optionally an uncovered area of the current collector. For stacked cells having multiple anodes and cathodes, the tabs may be welded together to form a single positive tab and a single negative tab for connection to an external circuit.
[0036] The cathode in the electrochemical cells provided herein serves as a positive electrode. The cathode comprises an electrochemically active polycrystalline cathode material capable of absorbing and desorbing Li. The electrochemically active cathode material provided herein has the formula Li 1+x MO 2+yThe material is represented by the formula: where -0.9≦x≦0.3, -0.3≦y≦0.3, and M comprises 80 atomic percent or more of Ni relative to the total of M. The polycrystalline material comprises an aggregate or cluster of a plurality of crystallites to form the polycrystalline material. Within the polycrystalline material, each crystallite may have any suitable shape, which may be the same or different within each secondary particle of the electrochemically active cathode material. Furthermore, the shape of each crystallite may be the same or different in different particles. Depending on the crystalline nature of the crystallites, the crystallites may have facets, the crystallites may have multiple planes, and the shape of the crystallites may approximate a geometric shape. The crystallites may optionally be polyhedral. The crystallites may have a linear shape, and in their cross-sectional view, a portion or the entire crystallite may be linear. The crystallites may be square, hexagonal, rectangular, triangular, or combinations thereof.
[0037] The electrochemically active cathode material comprises Ni as a major portion of the M component. Optionally, the amount of Ni in the first composition is between 80 atomic percent and 100 atomic percent (at%) of the total M. Optionally, the Ni component of M is 80 at% or greater. Optionally, the Ni component of M is 85 at% or greater. Optionally, the Ni component of M is 90 at% or greater. Optionally, the Ni component of M is 95 at% or greater. Optionally, the Ni content of M is 75 at% or more, 76 at% or more, 77 at% or more, 78 at% or more, 79 at% or more, 80 at% or more, 81 at% or more, 82 at% or more, 83 at% or more, 84 at% or more, 85 at% or more, 86 at% or more, 87 at% or more, 88 at% or more, 89 at% or more, 90 at% or more, 91 at% or more, 92 at% or more, 93 at% or more, 94 at% or more, 95 at% or more, 96 at% or more, 97 at% or more, 98 at% or more, 99 at% or more, 99.5 at% or more, 99.9 at% or more, or 100 at%.
[0038] In some embodiments, M is Ni alone or in combination with one or more additional elements. Optionally, the additional element is a metal. Optionally, the additional element may include one or more of Al, Mg, Co, Mn, Ca, Sr, Zn, Ti, Y, Cr, Mo, Fe, V, Si, Ga, or B. In certain embodiments, the additional element may include Mg, Co, Al, or a combination thereof. Optionally, the additional element may be Mg, Al, V, Ti, B, or Mn, or a combination thereof. Optionally, the additional element is selected from the group consisting of only Mg, Al, V, Ti, B, or Mn. Optionally, the additional element is selected from the group consisting of only Mg, Co, and Al. Optionally, the additional element is selected from the group consisting of only Ca, Co, and Al. In some embodiments, the additional element is Mn or Mg, or both Mn and Mg. Optionally, the additional element is Mn, Co, Al, or any combination thereof. Optionally, the additional elements include Co and Mn. Optionally, the additional elements are Co and Al. Optionally, the additional element is Co.
[0039] The additional element M in the electrochemically active cathode material may be present in an amount of about 0.1 to about 20 at%, specifically about 5 to about 20 at%, more specifically about 10 to about 20 at%, of M in the first composition. Optionally, the additional element may be present in an amount of about 1 to about 20 at%, specifically about 2 to about 18 at%, more specifically about 4 to about 16 at%, of M in the first composition. In some illustrative examples, M is about 80-100 at% Ni, 0-15 at% Co, 0-15 at% Mn, and 0-10 at% additional element.
[0040] The electrochemically active cathode material used in the cathode of the cells provided herein includes Co. The Co is distributed non-uniformly throughout, on, or within the secondary particles of the electrochemically active cathode material. A non-uniform distribution is a distribution of Co that varies throughout some or all of the secondary particles. In some embodiments, the polycrystalline material includes grain boundaries between adjacent crystallites within the secondary particles. The concentration of cobalt, aluminum, or both at the grain boundaries is higher than the concentration at the centers of adjacent crystallites. Such materials are considered to be grain boundary enriched materials. Illustrative examples of such grain boundary enriched materials can be found in U.S. Pat. No. 9,391,317 and U.S. Patent Application Serial No. 16 / 250,762.
[0041] In certain embodiments, the secondary particles used as electrochemically active cathode materials have grain boundaries enriched in Co, Al, or both, and optionally the mole fraction of Co, Al, or both at the grain boundaries is higher than the mole fraction of Co, Al, or both in the crystallites (optionally on average over the sum of the respective domains).
[0042] The composition of the crystallites, the grain boundary regions, or both, optionally have a layered α-NaFeO2 type structure, a cubic structure, or a combination thereof. An embodiment is specifically described in which the grain boundaries have a layered α-NaFeO2 type structure. Another embodiment is specifically described in which the grain boundaries have a defective α-NaFeO2 type structure. Another embodiment is specifically described in which a portion of the grain boundaries has a cubic or spinel structure.
[0043] The grain boundary may optionally be represented by the formula I, Li 1+x MO 2+yThe second composition is represented by Formula 1, wherein -0.9≦x≦0.3, -0.3≦y≦0.3, and M includes Co, Al, or a combination of Co and Al. Optionally, M in the second composition further includes Ni. Optionally, the Ni content of M in the second composition is 1 at% or less. Optionally, the Ni content of M is 5 at% or less. Optionally, the Ni content of M is 10 at% or less. Optionally, the Ni content of M is 20 at% or less. Optionally, the Ni content of M is 75 at% or less. Optionally, the Ni content of M is 80 at% or less. Optionally, the Ni content of M is 90 at% or less. Optionally, the Ni content of M is 95 at% or less. Optionally, the Ni content of M is 98 at% or less. Optionally, the Ni content of M is 99 at% or less.
[0044] In the electrochemically active grain boundary strengthened cathode material, the concentration of Co, Al, or both averaged through the grain boundary region is higher than the average concentration of Co, Al, or both averaged through the crystallite region. Thus, the mole fraction of Co, Al, or both at the grain boundary is higher than the mole fraction of Co, Al, or both in the crystallite. If any Co, Al, or both that defines the crystallite composition is present in the crystallite, the mole fraction of Co, Al, or both in the first composition is lower than the total mole fraction of Co or Al, alone or in combination, in the whole grain composition as determined by ICP. The mole fractions of Co and Al, alone or in combination, in the crystallite may be zero. The mole fractions of Co and Al, alone or in combination, in the second composition that defines the grain boundary are higher than the mole fractions of Co and Al, alone or in combination, in the whole grain as measured by ICP. The second composition may be enriched with 0 at% or 8 at% Co or therebetween, optionally with 3 at% or 5 at% Co or therebetween, and may be optionally supplemented with 0.01 at% to 10 at% Al, optionally up to 1.5 at% Al.
[0045] Optionally, the second composition and the first composition (the microcrystalline composition) are identical except for the presence or increased concentration (molar fraction) of Co, Al, or both in the second composition compared to the first composition.
[0046] The electrochemically active cathode material optionally includes a non-uniform distribution of Co within the secondary particles. The non-uniform distribution is in the form of a gradient of Co within the crystallite, within the entire secondary particle, or a combination thereof. Optionally, the crystallite includes a gradient of Co concentration, in which the amount of Co at or near the periphery of the crystallite is higher than the concentration of Co at or near the center of the crystallite. Illustrative examples of such materials can be found in Lim, et al., Adv. Funct. Mater. 2015; 25:4673-4680 or Lee et al., Journal of Power Sources, 2015; 273:663-669.
[0047] In some embodiments, a non-uniform distribution of Co is achieved by coating the core with Co, such as described in U.S. Pat. No. 7,381,496, U.S. Patent Application Publication No. 2016 / 0181611, or Zuo, et al., Journal of Alloys and Compounds, 2017; 706:24-40.
[0048] The positive electrode may be provided by combining lithium nickel oxide, a conductive agent, and a binder and providing a coating comprising the lithium nickel oxide, the conductive agent, and the binder on a current collector. The conductive agent may be any conductive agent that provides suitable properties and may be amorphous, crystalline, or a combination thereof. The conductive agent may include carbon black, such as acetylene black or lamp black, mesocarbon, graphite, carbon fiber, carbon nanotubes, such as single-walled or multi-walled carbon nanotubes, or a combination thereof.
[0049] The binder used in either the anode or cathode may be any binder that provides suitable properties and may include, but is not limited to, polyvinylidene fluoride, copolymers of polyvinylidene fluoride, polyvinylidene difluoride (PVDF), hexafluoropropylene, polyvinyl acetate, poly(vinyl butyral-vinyl alcohol-vinyl acetate copolymer), poly(methyl methacrylate-ethyl acrylate copolymer), polyacrylonitrile, polyvinyl chloride-vinyl acetate copolymer, polyvinyl alcohol, poly(1-vinylpyrrolidone-vinyl acetate copolymer), cellulose acetate, polyvinylpyrrolidone, polyacrylates, polymethacrylates, polyolefins, polyurethanes, polyvinyl ethers, acrylonitrile-butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene-styrene, sulfonated styrene / ethylene-butylene / styrene triblock polymers, polyethylene oxide, or combinations thereof.
[0050] The positive electrode may be prepared by combining the lithium nickel oxide, the conductive agent, and the binder in appropriate ratios (e.g., 80-99 weight percent lithium nickel oxide, 0.5-20 weight percent conductive agent, and 0.5-10 weight percent binder) based on the total weight of the lithium nickel oxide, conductive agent, and binder. The lithium nickel oxide, conductive agent, and binder may be suspended in a suitable solvent, such as N-methylpyrrolidinone or other suitable solvent, placed on a suitable substrate, such as aluminum foil, and dried in air to provide the positive electrode.
[0051] The electrochemical cell provided herein further comprises a negative electrode. The negative electrode is a Li / Li + Optionally, the electrochemically active negative electrode material includes an electrochemically active negative electrode material defined by a redox potential of 400 mV or more at Li / Li. +is 400mV or more, optionally 500mV or more, optionally 600mV or more, optionally 700mV or more, optionally 800mV or more, optionally 900mV or more, optionally 1V or more, optionally 1.1V or more, optionally 1.2V or more, optionally 1.3V or more, optionally 1.4V or more, optionally 1.5V or more, optionally 1.55V or more, optionally 1.6V or more.
[0052] An illustrative example of an electrochemically active anode material is the Li / Li + The oxides include, but are not limited to, oxides of Nb, Sn, Sb, Ti, Si, and combinations of these elements, as long as they are defined by a redox potential of 400 mV or greater at 1000 . Illustrative examples can be found in Han and Goodenough, Chemistry of Materials, 23, no. 15 (2011): 3404-3407.
[0053] In some embodiments, the electrochemically active negative electrode material comprises an oxide of Nb. 16 W5O 55 , Nb 18 W 16 O 93 , TiNb2O7, Ti2Nb2O9, LiTiNbO5, KNb5O 13 , and K6Nb 10.8 O 30 Such materials include, but are not limited to, those described in Griffith, et al., Nature, 559, no. 7715 (2018): 556-563.
[0054] Other examples of oxides that can be used as electrochemically active negative electrode materials include SnO2, Sb2O3, SiO, SiO2, and conversion type anodes. + It is characterized by a redox potential of 400 mV at .
[0055] In some embodiments, the electrochemically active negative electrode material comprises an oxide of Ti, which may be in any form and optionally includes nanowires, such as the TiO2-B nanowires described in Armstrong, et al., Journal of Power Sources, 146, no. 1-2 (2005): 501-506.
[0056] An illustrative example of an oxide of titanium is lithium titanium oxide (LTO), which has a pair Li / Li + higher than 1V (optionally vs. Li / Li + The anode optionally has an electrochemical redox potential of about 1.5 V at 2000. The lithium titanium oxide may have a spinel structure. The anode optionally has a structure of the formula Li 4+a Ti5O 12+b In some embodiments, the lithium titanium oxide may include an electrochemically active anode material represented by Formula 3: Li 4+y Ti5O 12 (3) In the formula, 0≦y≦3, 0.1≦y≦2.8, or 0≦y≦2.6.
[0057] Alternatively, the lithium titanium oxide may be represented by Formula 4: Li 3+z Ti 6-z O 12 (4) In formula 4, 0≦z≦1. Optionally, 0≦z≦1, 0.1≦z≦0.8, or 0≦z≦0.5. A combination of electrochemically active anode materials including at least one of the lithium titanium oxides above may be used. In some embodiments, the electrochemically active anode material has a ratio of Li / Li + Li4Ti5O has an electrochemical redox potential of about 1.55 V at 12 or the Li4Ti5O 12 It is.
[0058] The electrochemically active anode material may have any suitable particle size, such as a particle size of from 0.1 μm to 100 μm, or from 1 μm to 10 μm.
[0059] The electrochemically active anode material is 4m 2 / g~20m 2 / g or 7m 2 / g~13m 2 The material may have a high specific surface area (SSA), such as 0.1 g / g.
[0060] The negative electrode includes a current collector. As further described above (but without wishing to be bound by theory), it is understood that the electrochemical potential of the electrochemically active anode material is Li / Li + Since the negative electrode current collector has a potential of 400 mV or more at Li / Li, the negative electrode current collector may contain metals other than copper. This is because other metals such as aluminum and titanium have a potential of 400 mV or more at Li / Li. + This is to provide adequate stability at potentials present when electrochemically active anode materials are used that have an electrochemical redox potential of 400 mV or more at Li / Li. Without wishing to be bound by theory, it is understood as follows. At potentials of 0.1 V to 0.5 V vs. lithium, metals such as aluminum have electrochemical reactivity with lithium, whereas copper does not. For this reason, copper is used as the current collector material when graphite is used as the anode material. Thus, at potentials of 0.1 V to 0.5 V vs. Li, + Current collectors that include a metal that is electrochemically reactive with lithium at potentials of 0.1 V to 0.5 V, 0.15 V to 0.45 V, or 0.2 V to 0.4 V at low potential cannot be used with graphite anode materials, but may be used with the anode materials provided herein.
[0061] The current collectors of the anode, cathode, or both may comprise aluminum. Aluminum or aluminum alloys are mentioned. Representative aluminum alloys include aluminum alloys 1050, 1100, 1145, 1235, 1350, 3003, 3105, 5052, and 6061.
[0062] The negative electrode may be formed by combining an electrochemically active anode material, a conductive agent, and a binder, and providing a coating comprising the electrochemically active anode material, the conductive agent, and the binder on a current collector selected for the negative electrode. The conductive agent may be any conductive agent that provides suitable properties and may be amorphous, crystalline, or a combination thereof. The conductive agent may be carbon black, such as acetylene black or lamp black, mesocarbon, graphite, carbon fiber, carbon nanotubes, such as single-walled or multi-walled carbon nanotubes, or a combination thereof. The binder may be any binder that provides suitable properties and may include, for example, polyvinylidene fluoride, PVDF, copolymers of polyvinylidene fluoride and hexafluoropropylene, polyvinyl acetate, poly(vinyl butyral-vinyl alcohol-vinyl acetate copolymer), poly(methyl methacrylate-ethyl acrylate copolymer), polyacrylonitrile, polyvinyl chloride-vinyl acetate copolymer, polyvinyl alcohol, poly(1-vinylpyrrolidone-vinyl acetate copolymer), cellulose acetate, polyvinylpyrrolidone, polyacrylates, polymethacrylates, polyolefins, polyurethanes, polyvinyl ethers, acrylonitrile-butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene-styrene, sulfonated styrene / ethylene-butylene / styrene triblock polymers, polyethylene oxide, or combinations thereof.
[0063] A negative electrode may be fabricated by combining an electrochemically active anode material, a conductive agent, and a binder in appropriate ratios (e.g., 80-98 weight percent electrochemically active anode material, 2-20 weight percent conductive agent, and 2-10 weight percent binder) based on the total weight of the electrochemically active anode material, conductive agent, and binder. The electrochemically active anode material, conductive agent, and binder may be suspended in a suitable solvent, such as N-methylpyrrolidinone, placed on a suitable current collector, such as aluminum, titanium, or stainless steel, and dried in air to provide a negative electrode.
[0064] Positive and negative electrodes may be prepared with a loading (mass of coating material per unit area of current collector) tailored to the rate capability and voltage range required for a particular application. Higher power (higher rate) applications require lower loading electrodes to maximize the interfacial surface area of the electrodes and minimize current density. On the other hand, applications requiring higher energy density require higher loading electrodes to minimize the content of non-active materials such as current collectors and separators in the cell.
[0065] Li / Li + An additional advantage of electrochemically active anode materials having an electrochemical redox potential of 400 mV or greater at 1000 V is that they may be realized in cell designs that are anode-regulated because their potential is sufficiently positive to avoid the possibility of lithium metal plating under the most severe overcharge conditions. Such anode-regulated cell designs may improve the overcharge resistance and stability of the cell by limiting the delithiation of a charged cathode to a level comparable to the voltage per cell required in a particular application. Thus, the electrochemical cells provided herein are optionally limited, either in area, packing factor, or otherwise.
[0066] Optionally, the electrochemical cell is anode-regulated such that the geometric surface area of the cathode is optionally equal to or greater than the geometric surface area of the anode. Thus, the area ratio, which is equal to the area of the negative electrode divided by the area of the positive electrode, is 1 or less. Optionally, the area ratio of the anode to the cathode is 0.99 or less, 0.98 or less, 0.97 or less, 0.96 or less, 0.95 or less, 0.94 or less, 0.93 or less, 0.92 or less, 0.91 or less, 0.90 or less, 0.85 or less, 0.80 or less, 0.75 or less, 0.70 or less, 0.65 or less, 0.60 or less, 0.55 or less, or 0.50 or less. In some embodiments, the geometric areas of the positive and negative electrodes are the same or nearly the same.
[0067] Optionally, the capacity ratio of the anode to the cathode is 1 or less. The electrode capacity ratio is the ratio of the negative electrode capacity to the positive electrode capacity. The capacity of an electrode is often given as the product of the charge time per unit area. The units of charge and time used are not important in the ratio calculation. The capacity of an electrode is equal to the capacity per unit area multiplied by the area of the electrode. Thus, for similar areas of two electrodes, the capacity ratio is equal to the ratio of the capacitances per unit area of the two electrodes. Optionally, the capacity ratio of the anode to the cathode is 0.99 or less, 0.98 or less, 0.97 or less, 0.96 or less, 0.95 or less, 0.94 or less, 0.93 or less, 0.92 or less, 0.91 or less, 0.90 or less, 0.85 or less, 0.80 or less, 0.75 or less, 0.70 or less, 0.65 or less, 0.60 or less, 0.55 or less, or 0.50 or less.
[0068] The ideal anode / cathode (n / p) ratio depends on the particular cathode material used and the intended application of the cell. As described herein, the maximum n / p capacity ratio is less than 1 (e.g., 0.99), since it is believed that an n / p ratio less than 1 maximizes the benefits. At the other extreme, an n / p ratio less than 0.5 significantly limits the commercial viability of the cell, since an n / p ratio less than 0.5 means that only 50% of the capacity of the cathode material is utilized. Between 0.5 and 0.99, the cell designer will easily determine where to limit the upper voltage termination limit of the cathode material. For example, cathode instability, side reactions, or electrolyte decomposition may occur at the Li / Li + Therefore, in the cells provided herein, the voltage is increased relative to Li / Li to achieve a long-life cell. + The desired n / p ratio may be determined by the following equation:
number
[0069] In the formula, Q Max Voltage is the capacity of the cathode material at the maximum voltage during charging, and Q Voltage Limit is the capacity of the cathode material at the voltage limit imposed during charging. From this equation, it can be determined that the optimum n / p capacity ratio is less than 1, optionally between 0.5 and 0.99, optionally between 0.7 and 0.99, optionally between 0.8 and 0.99, optionally between 0.8 and 0.97, optionally between 0.8 and 0.96, optionally between 0.8 and 0.95, optionally between 0.85 and 0.99, optionally between 0.85 and 0.97, optionally between 0.85 and 0.95, optionally between 0.9 and 0.99, optionally between 0.9 and 0.97, optionally between 0.9 and 0.95.
[0070] In some embodiments of the electrochemical cell provided, the unit cell comprises an anode, a cathode, and a separator located between the anode and the cathode, with an electrolyte in ionic contact with the anode and the cathode. Optionally, the unit cell includes a double-sided anode. The electrochemically active anode material is coated on both sides of the current collector, or the cathode is a double-sided cathode, with the electrochemically active cathode material coated on both sides of the current collector. This double-sided electrode may be flanked by two opposing single-sided electrodes or other opposing double-sided electrodes. In this manner, an electrode stack may be provided to form the unit cell. In some embodiments, two single-sided anode electrodes incorporating electrochemically active anode material coated on an aluminum current collector, a polyolefin separator, and a double-sided cathode electrode coated on both sides of the aluminum current collector are provided. Such unit cells are stacked to form an electrochemical cell. In some embodiments, a single-sided anode electrode is located at the end of such a stack. However, it is understood that the terminal electrode of the stack may also be the cathode.
[0071] The positive electrode, negative electrode, and separator may be combined in a housing to provide a lithium-ion cell. One embodiment of this is illustrated in FIG. The lithium-ion cell 100 includes a positive electrode 101 having a positive electrode tab 101', a negative electrode 102 having a negative electrode tab 102', and a separator 103 interposed between the positive electrode 101 and the negative electrode 102. The cell may include an electrolyte in ionic contact with both the anode and the cathode. Ionic contact means that the electrolyte can transfer ions from the anode to the cathode or from the cathode to the anode.
[0072] The electrochemical cell includes a separator located between the anode and the cathode in the unit cell. The separator may be comprised of a microporous membrane, a porous film, optionally including a polyolefin, such as polypropylene, polyethylene, or a combination thereof. In some embodiments, the separator may further include a coating of a ceramic oxide material, optionally aluminum oxide, or a particulate reinforcing filler. A high permeability separator having a Gurley air permeability of less than 200 seconds per 100 cc may be selected to provide a cell with high power performance.
[0073] The anode, cathode, separator, and electrolyte may be housed in a cell case (e.g., a housing). The cell case 110 may be a metal can or a laminate film, such as a heat-sealable aluminum foil, such as an aluminum-coated polypropylene film. Thus, the electrochemical cells provided herein may have any known cell shape. Examples include button cells, pouch cells, cylindrical cells, or other suitable configurations. In some embodiments, the housing is a flexible film, optionally a polypropylene film. Such housings are commonly used to form pouch cells. The lithium-ion cells may have any suitable configuration or shape, and may be cylindrical or prismatic.
[0074] The cells provided herein optionally exclude any circuitry, such as battery management circuitry, or other means used in the art that can regulate the charge rate or degree of charge or discharge.
[0075] The lithium ion cell includes an electrolyte in contact with the positive electrode 101, the negative electrode 102, and the separator 103. The electrolyte may include an organic solvent and a lithium salt. The organic solvent may be a mixture of cyclic carbonates, linear carbonates, and esters. Exemplary organic solvents include ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, methyl butyrate, or combinations thereof. A mixture of propylene carbonate, ethyl methyl carbonate, and methyl butyrate is mentioned.
[0076] Representative lithium salts used in the electrolyte include, but are not limited to, LiPF6, LiBF4, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiN(SO2C2F5)2, LiSbF6, LiC(CF3SO2)3, LiC4F9SO3, and LiAlCl4. The lithium salt may be dissolved in an organic solvent. Combinations comprising at least one of the above salts and solvents may be used. The concentration of the lithium salt may be 0.1 to 2 molar (M) in the electrolyte. A solution of 1 M LiPF6 is described.
[0077] The electrolyte may be formulated to provide high power and low temperature performance. Such electrolytes may have an ionic conductivity of greater than 8 mS / cm at 25° C. and greater than 1 mS / cm at −40° C.
[0078] Batteries made from the present lithium-ion cells may include any suitable number of cells (e.g., 1-50,000, 2-25,000, 4-15,000, 8-5,000, 16-2,000, or 32-1,000). The cells may be connected in any suitable configuration, including series, parallel, or combinations thereof.
[0079] The cells and batteries made therefrom may be charged and discharged in any suitable manner, including at any suitable rate, such as 100C or less, 10C or less, 0.01C to 10C, or 0.1C to 1C. The C-rate is the discharge rate of the cell, calculated by dividing the total capacity of the cell by the total discharge time. For example, the C-rate of a battery with a discharge capacity of 1.6 amp-hours is 1.6 amps. The discharge may be to 1.4V or less, optionally 1.3V or less, optionally 1.2V or less, optionally 1.1V or less, optionally 1.0V or less, optionally 0.9V or less, optionally 0.8V or less, optionally 0.7V or less, optionally 0.6V or less, optionally 0.5V or less, optionally 0.4V or less, optionally 0.3V or less, optionally 0.2V or less, optionally 0.1V or less, for example, 0.1V to 0.001V, 0.05V to 0.005V. The discharge may optionally be to 0V or less.
[0080] Various aspects of the present disclosure are illustrated by the following non-limiting examples, which are intended for illustrative purposes and are not intended to limit any practice of the present invention, and it will be understood that variations and modifications are possible without departing from the spirit and scope of the present invention. EXAMPLES
[0081] Example 1 The positive electrode has the formula Li 1.01 Mg 0.025 Ni 0.88 Co 0.12 Al 0.0064 A mixture of cobalt grain boundary reinforced LNO-type lithium nickel oxide (CAMX Power, LLC, Lexington, MA), acetylene black, and polyvinylidene difluoride (PVDF) in a weight ratio of 94:3:3, represented by O2, was deposited on aluminum at 11.3 mg / cm. 2 The negative electrode was fabricated by coating with an active material filling rate of Li4Ti5O 12 and 10m 2A mixture of lithium titanium oxide, acetylene black, and PVDF in a weight ratio of 90:3:7 having a specific surface area of 12.7 mg / cm2 / g was applied to aluminum. 2 The active material was coated at a loading rate of 100m 2 Acetylene black (obtained from Denka Carbons as Denka AB-100) having a surface area of 1000000-1200000 mol / g and PVDF (obtained from Solvay Chemicals as Solef 5130) having a molecular weight in the range of 1,000,000-1,200,000 mol / g were used for both the positive and negative electrodes.
[0082] The positive and negative electrodes have the same geometric area of 72.7 cm 2 The twelve double-sided positive electrode layers were stacked together with the eleven double-sided and two single-sided negative electrode layers in a Z-fold separator assembly. The separator was a 21 μm thick alumina-coated polyolefin material with a Gurley air permeability of 110 seconds. The electrode stack assembly was placed into an aluminized polypropylene housing with the electrode tabs feeding through the end seals of the package. An electrolyte consisting solely of 1 M LiPF6 in a mixture of propylene carbonate, ethyl methyl carbonate and methyl butyrate in a 1:1:2 weight ratio, with ionic conductivity of 11 mS / cm at 25°C and 2 mS / cm at -40°C, was added prior to sealing to yield a 3 Ampere-hour (Ah) laminate-packed prismatic cell weighing 82 g.
[0083] The cell was cycled at room temperature between 2.75 V and 1.4 V at various rates. The cell was also cycled at −50° C. between 3.0 V and 1.2 V at various rates.
[0084] FIG. 2 is a graph of cell voltage (Volts (V)) versus capacity (Amp-hours (Ah)). The graph illustrates the voltage profile of the first charge / discharge of this cell at a rate of 0.6 A and subsequent charge / discharge at rates of 3 A and 9 A, conducted at room temperature. The voltage profile of the first charge at 0.6 A shows a rise at about 2.55 V that is typical of the anode-regulated charge capacity of this design. The cell has high rate capability, as indicated by the modest increase in polarization voltage as the current increases from 0.6 A (C / 5) to 9 A (3C).
[0085] FIG. 3 is a graph of cell voltage (volts (V)) versus capacity (ampere-hours (Ah)). The graph illustrates the voltage profile of the cell being charged and discharged at various rates at -50°C. This voltage profile represents a high level of performance at temperatures well outside the range available with conventional lithium-ion battery technology. To accommodate the higher polarization voltage at this extremely low temperature, the voltage limits are extended compared to the voltage limits for room temperature cycling (FIG. 4). The cell delivers more than half its capacity when discharged at 0.6A and more than 40% of its capacity when discharged at 10C. Notably, the cell can be charged to nearly half its capacity at a rate of 3A (1C) within the 3V charge voltage limit.
[0086] Example 2 Two 120mAh laminate-packaged prismatic cells were made using the materials and methods of Example 1, with the following differences:
[0087] The loading rate of the active cathode material is 9.0 mg / cm 2 and the loading rate of the active negative electrode material is 9.4 mg / cm 2 The individual cathode and anode pieces both had an area of 10.2 cm 2and assembled into a stack with five double-sided positive layers, four double-sided negative layers, and two single-sided negative layers. The cells were first cycled at room temperature between 2.43 V and 1.33 V, which corresponds to cycling a six-series cell battery between 14.6 V and 8.0 V. The cells were then cycled 1000 times between 2.43 V and 1.33 V in a 45° C. oven at a charge rate of 1.2 A (10 C) and a discharge rate of 1.2 A (10 C). The cells were self-supporting during this cycling with no external attachments to maintain stack pressure in case they outgas. Inspection and measurement of the cells after cycling was completed showed no evidence of the cells outgassing.
[0088] Figure 4 is a graph of the discharge capacity at 10 C for both cells versus cycle number during cycling at 45° C. Figure 4 shows that the capacity delivered by the cells only decreased by about 5% during this aggressive cycling regime, indicating that the cells had excellent temperature stability and were not damaged by repeated fast charging.
[0089] Example 3 A 325 mAh laminate-packaged prismatic cell designed for extremely high power performance was constructed using the materials and methods of Example 1, with the following differences:
[0090] The loading rate of the active cathode material is 3.6 mg / cm 2 and the loading rate of the active negative electrode material is 3.7 mg / cm 2 The individual cathode and anode pieces had an area of 10.2 cm 2 and assembled into a stack with 36 double-sided positive electrode layers, 35 double-sided negative electrode layers, and 2 single-sided negative electrode layers. The separator was a 6 μm thick polyolefin material with a Gurley air permeability of 100 seconds. The completed cell weighed 13.5 g and had a volume of 7.2 cc.
[0091] The cell was cycled at room temperature between 2.59V and 1.31V at various constant power levels, which corresponds to cycling an 11-cell battery in series between 28.5V and 14.4V. Figure 5 shows two plots of voltage (Volts (V)) versus capacity (mAh) at various power levels for charging and discharging the cell, respectively, demonstrating the remarkably high power performance of the cell. At a constant power of 80W, which corresponds to a constant specific power of over 5kW / kg and a power density of over 11kW / l, the cell sustains continuous charging for nearly 30 seconds and continuous discharging for about 11 seconds, delivering 18.5Wh / kg, which constitutes about 45% of its capacity and about 35% of its total energy content.
[0092] Example 4 A three-electrode 130 mAh laminate-packaged prismatic cell containing a Li metal reference electrode was constructed using the materials and methods of Example 1, with the following differences:
[0093] The loading rate of the active cathode material is 9.1 mg / cm 2 and the loading rate of the active negative electrode material is 10.0 mg / cm 2 The individual cathode and anode pieces had an area of 10.2 cm 2 and were assembled into a stack having five double-sided positive electrode layers, four double-sided negative electrode layers, and two single-sided negative electrode layers.
[0094] The performance of the cell was characterized by constant current continuous and pulse charge / discharge cycling between 2.59 V and 1.31 V at room temperature and -18°C, and the cathode potential was monitored by measuring the positive electrode voltage against a Li metal reference electrode while cycling the cell, and the anode (negative electrode) potential was calculated by the difference between the cathode potential and the cell voltage. The cell was then discharged to 0 V and held at that voltage for 24 hours. The cell was then voltage reversed by overdischarging the cell for an additional 5% of its capacity (6.5 mAh) at a rate of 0.1 C (i.e., 13 mA discharge for 30 minutes). After polarity reversal, the cell was recharged and its performance was characterized again.
[0095] FIG. 6 is a graph of electrode potential (V vs. Li) and cell voltage versus time (min) for a 30 minute cell overdischarge and a subsequent 30 minute relaxation at open circuit. The graph shows that the cell voltage reversed and reached about −3.5 V, and that the cathode and anode potentials reached about 1.9 V vs. Li and about 5.4 V vs. Li, respectively. At open circuit, the cell voltage increased rapidly, mainly due to a rapid decrease in the high anode potential, while the low cathode potential increased much more slowly. This indicates that the polarization voltage at the anode was higher than the polarization voltage at the cathode during overdischarge and cell repolarization, indicating that the charge passed by the cathode during overdischarge was coupled to a reversible faradaic process.
[0096] FIG. 7 is a graph of capacity (Ah) versus voltage (volts) at various rates of discharge at room temperature of the cell before and after it was reversed, and shows that the effect of the 5% capacity reversal on the discharge characteristics at room temperature was minimal.
[0097] Figure 8 is a graph of capacity (mAh) versus voltage (volts) for 30 second consecutive pulse discharges at 10C (1.3A) at -18°C of the cell before and after it was reversed. The cell was allowed to sit at open circuit for 30 minutes after each pulse (before the next pulse) to ensure that no significant self-heating of the cell occurred during testing. The cell was able to sustain this aggressive low temperature pulsation over 50% of its state of charge range (65mAh) both before and after it was reversed, indicating that the impact of the 5% capacity reversal on low temperature pulse power performance was minimal.
[0098] Example 5 A three-electrode 130 mAh laminate-packaged prismatic cell containing a Li metal reference electrode was prepared using the materials and methods of Example 4. The performance of the cell was characterized by constant current continuous and pulse charge-discharge cycling between 2.59 V and 1.31 V at room temperature and -18°C, and the cathode potential was monitored by measuring the positive electrode voltage relative to the Li metal reference electrode while cycling the cell. The anode (negative electrode) potential was calculated by the difference between the cathode potential and the cell voltage. The cell was then charged to 2.59 V. The cell was then overcharged by an additional 10% of its capacity (13 mAh) at a rate of 0.1 C (i.e., 13 mA charge for 60 minutes). After overcharging, the cell was discharged and its performance was recharacterized.
[0099] 9 is a graph of electrode potential (V vs. Li) and cell voltage versus time (min) for a 60 minute cell overcharge and a subsequent 30 minute relaxation at open circuit. The graph shows that the voltage of the overcharged cell reached about 3.5 V, and that the cathode and anode potentials were respectively 1.5 V vs. Li / Li + At about 4.1V and Li / Li + 0.6 V at 100° C. At open circuit, the cell voltage decreased with increasing anode potential, while the cathode potential remained unchanged. This indicates that the polarization voltage at the anode was higher than that at the cathode during overcharge, indicating that the charge passed by the cathode during overcharge was coupled to its normally reversible faradaic process, as expected for an anode-regulated cell design with approximately 20% excess cathode.
[0100] Figure 10 is a graph of capacity (Ah) versus voltage (Volts) at various rates of discharge at room temperature of the cell before and after it was reversed, showing that the effect of 10% overcharging on the discharge characteristics at room temperature was minimal. The polarization voltage during discharge at 25C was higher after overcharging than before overcharging, indicating that overcharging caused a slight increase in the impedance of the cell.
[0101] FIG. 11 is a graph of capacity (mAh) versus voltage (volts) for 30 second consecutive pulse discharges at 10C (1.3A) at -18°C of the cell before and after it was overcharged. The cell was allowed to sit at open circuit for 30 minutes after each pulse (before the next pulse) to ensure that no significant self-heating of the cell occurred during the test. The cell was able to sustain this low temperature pulsation over a 65mAh depth of discharge range before being overcharged and over a 50mAh depth of discharge range after being polarized reversed, while the polarization voltage during pulsation was higher after overcharging. These aggressive low temperature pulsation test results show that the impedance of the cell increased with overcharging, yet the cell maintained a high level of performance.
[0102] Example 6 A 2.5 Ah laminate-packed prismatic cell was constructed using the materials and methods of Example 1, with the following differences:
[0103] The loading rate of the active cathode material is 11.2 mg / cm 2 and the loading rate of the active negative electrode material is 12.6 mg / cm 2 The individual cathode and anode pieces had an area of 72.7 cm 2 and were assembled into a stack having 10 double-sided positive electrode layers, 9 double-sided negative electrode layers, and 2 single-sided negative electrode layers.
[0104] The cell was first charged to 2.75 V at 0.5 A and then cycled between 2.75 V and 1.4 V at various rates to evaluate its performance. The cell was then cycled 1000 times between 2.65 V and 1.4 V at room temperature with a charge rate of 2.5 A (1C) and a discharge rate of 2.5 A (1C). During this cycling, the cell continuously maintained a capacity of 2.2 Ah. After the 1000 cycles, the cell was discharged to 0 V and stored at room temperature for 33 months. After this storage, the cell voltage at open circuit was measured as 0 V, and the cell was then charged and cycled by the same protocol used to characterize the cell when it was assembled as new.
[0105] FIG. 12 is a graph of capacity (Ah) versus voltage (Volts) at various rates of discharge at room temperature for the cell before and after cycling it 1000 times and then storing it under 0V conditions for 33 months, and shows that the performance of the cell changed little with cycling and long-term storage at 0V. These results demonstrate the exceptional cycling stability and storage life under 0V conditions for this cell technology. The figure also shows that the first charge at 0.5A after long-term storage at 0V was essentially identical to the first charge at 0.5A of a brand new cell, indicating that discharging to 0V returned the cell to its brand new state.
[0106] Example 7 A 2.7 Ah laminate-packed prismatic cell was constructed using the materials and methods of Example 1, with the following differences:
[0107] The loading rate of the active cathode material is 8.4 mg / cm 2 and the loading rate of the active negative electrode material is 9.1 mg / cm 2 The individual cathode and anode pieces had an area of 72.7 cm 2 and were assembled into a stack having 15 double-sided positive electrode layers, 14 double-sided negative electrode layers, and 2 single-sided negative electrode layers.
[0108] This cell was first charged up to 2.65 V. Next, a stainless steel nail with a diameter of 2 millimeters (mm) having a blunt tip was pushed into this cell at a speed of 1 cm / second, and the nail was held in this cell for 1 minute while recording the voltage and surface temperature of this cell, whereby a nail penetration test was conducted on this cell in a custom-designed apparatus. Figure 13 is a graph of the cell voltage (V) and surface temperature (°C) before, during, and after the nail penetration test. This figure shows that while the nail was in this cell, the voltage of this cell decreased very slowly, similar to the voltage change during low-rate discharge (e.g., <C / 10). This indicates that a mild short circuit occurred. This voltage change stopped when the nail was pulled out. This indicates that the short circuit was removed. Similarly, the surface temperature of this cell increased only very slightly during nail penetration. These results represent a remarkable tolerance to the occurrence of high-power distributed internal short circuits in this cell technology when mechanical misuse involving penetration occurs.
[0109] Example 8 A 4 Ah laminated-packaged prismatic cell was fabricated using the materials and methods of Example 1, except for the following differences.
[0110] The filling rate of the active positive electrode material was 9.3 mg / cm 2 and the filling rate of the active negative electrode material was 9.0 mg / cm 2
[0111] Each cathode piece and anode piece had an area of 124.9 cm 2 and were assembled into a laminate having 12 double-sided positive electrode layers, 11 double-sided negative electrode layers, and 2 single-sided negative electrode layers.
[0112] The performance of the cell was first characterized by cycling the cell at room temperature between 2.59 V and 1.31 V at various rates, and then the cell was charged to 2.75 V. The charged cell was then crushed in a custom-designed device under a ½-inch diameter stainless steel bar placed across its 10 cm width for 5 minutes while recording the cell's voltage and surface temperature. During the crush test, the force on the bar was increased to 35 kN (3.8 tons). The displacement measured by the crushing device represented a reduction in the thickness of the cell in the direction of maximum fracture from 5 mm to 0.5 mm. During the crushing event, the cell's voltage slowly dropped like a low-rate discharge from 2.556 V to 2.552 V, and the surface temperature increased by 1° C. When the pressure on the bar and cell was released, the voltage stopped dropping and the temperature stopped increasing. The performance of the cell was then re-characterized by cycling it between 2.59V and 1.31V.
[0113] Figure 14 is a graph of capacity (Ah) versus voltage (Volts) for two rate discharges at room temperature of the present cell before and after it was subjected to a bar crush. This figure shows that the performance of the present cell was unaffected by the crush test, further demonstrating the remarkable resistance of the present cell technology to the development of high power dissipative internal short circuits when subjected to mechanical abuse.
[0114] Example 9 A 5 Ah laminate-packed prismatic cell was made using the materials and methods of Example 1, with the following differences:
[0115] The loading rate of the active cathode material is 9.5mg / cm 2 and the loading rate of the active negative electrode material is 9.1 mg / cm 2 The individual cathode and anode pieces had an area of 141.9 cm 2 and were assembled into a stack having 16 double-sided positive electrode layers, 15 double-sided negative electrode layers, and 2 single-sided negative electrode layers.
[0116] The cell of this embodiment has the following important elements: A negative electrode containing lithium titanium oxide (LTO) coated on an aluminum current collector. The coating is 10 μm thick. 2 The mixture is a 90:3:7 weight ratio mixture of LTO with a specific surface area of 1000 μm / g, acetylene black as a conductive additive, and PVDF as a binder. Acetylene black (obtained from Denka as Denka AB-100) is used for 100 m 2 / g surface area. The PVDF (obtained from Solvay as Solef 5130) has a molecular weight in the range of 1,000,000 to 1,200,000 mol / g. The acetylene black conductive carbon occupies less than 5% of the surface of the anode electrode. An uncoated strip of aluminum forms the negative tab. b. Overall composition Li coated on aluminum current collector 1.01 Mg 0.025 Ni 0.88 Co 0.12 Al 0.0064 A positive electrode containing high nickel cathode material with O2. The coating is a mixture of acetylene black and PVDF in a weight ratio of 94:3:3. Acetylene black is 100m 2 / g surface area and the PVDF has a molecular weight in the range of 1,000,000 to 1,200,000 mol / g. An uncoated strip of aluminum forms the positive electrode tab. c. A 21 μm thick polyolefin separator coated on one side with alumina and having a Gurley air permeability of 110 seconds, the alumina side being opposite the positive electrode. d. The geometric areas of the positive and negative electrodes are equal. e. An electrochemical cell was assembled using a stacked arrangement of a double-sided negative electrode, a separator, and a double-sided positive electrode. f. The lamination is such that the positive electrode tabs overlap each other and are ultrasonically welded to each other and to the positive cell tabs, and the negative electrode tabs overlap each other and are ultrasonically welded to each other and to the negative cell tabs. g. The end layer of the laminate is the negative electrode. h. An electrolyte having 1 M LiPF6 in a 1:1:2 mixture of propylene carbonate, ethyl methyl carbonate, and methyl butyrate by weight, having an ionic conductivity of 11 mS / cm at 25° C. and 2 mS / cm at −40° C.
[0117] The performance of the cell was characterized by charging and discharging at 2A and 8A between 2.65V and 1.5V at room temperature, then the cell was charged to 2.65V. The charged cell was then subjected to three nail penetration tests as per Example 7. The cell was then subjected to two crush tests as per Example 8. An array of three parallel green LEDs contacting across the terminals of the cell remained illuminated during all five abuse tests. The performance of the abused cell was then characterized again by charging and discharging at 2A and 8A between 2.65V and 1.5V, then the cell was continuously cycled between 2.65V and 1.4V at a charge and discharge rate of 5A.
[0118] Figure 15 is a picture of the cell after abuse testing, with the lit LED still in contact across the cell's terminals. Figure 15 clearly shows the remarkable abuse tolerance of the cell.
[0119] FIG. 16 is a graph of capacity (Ah) versus voltage (volts) at 8 A discharge at room temperature for the cell before and after it was subjected to five abuse tests, showing that the cell's performance was not affected by the repeated mechanical abuse.
[0120] FIG. 17 is a graph of the discharge capacity of the cell versus cycle number when the cell was charge cycled at 5A and discharge cycled at 5A at room temperature in ambient atmosphere after five abuse tests. The figure shows that the capacity delivered by the cell decreased in the first about 5 days (50+ cycles). This is likely due to the electrolyte losing volatile solvent components through the holes in the packaging caused by the nail penetration. The cell then cycled very stably at about 4Ah capacity for nearly 3 weeks without any further significant capacity loss, up to a point where over 300 cycles had elapsed. The degradation in the cell's performance at this point is likely due to the gradual infiltration of accumulated atmospheric moisture through the nail holes in the packaging. These results indicate that the only impact of the severe puncture and crushing abuse on the cell performance was due to damage to the packaging, further demonstrating the exceptional robustness of this cell technology.
[0121] Example 10 A 2.5 Ah laminate-packaged prismatic cell was fabricated according to the method of Example 9. The cell was charged to 2.75 V and then discharged to 1.4 V at currents of 0.5 A, 2.5 A, and 9.8 A, respectively. The voltage-capacity plot can be seen in FIG. 18. After this test, the cell was cycled 1000 times between 1.4 V and 2.75 V at a current of 2.5 A, both charging and discharging. The cell was then discharged to 0 V and stored unconnected and unmonitored for 33 months. After storage, the cell was charged to 2.75 V and discharged to 1.4 V at currents of 0.5 A, 2.5 A, and 9.8 A, respectively. On the voltage-capacity plot of FIG. 18, the solid line represents the performance of the cell as-prepared, and the dashed line represents the performance after storage.
[0122] It will be understood that, although the terms "first", "second", "third", etc. may be used herein to describe various elements, components, regions, layers, and / or sections, these elements, components, regions, layers, and / or sections should not be limited by these terms. These terms are used only to distinguish one element, component, region, layer, or section from another element, component, region, layer, or section. Thus, a "first element", "first component", "first region", "first layer", or "first section" discussed below can be referred to as a second element, second component, second region, second layer, or second section without departing from the teachings herein.
[0123] The terminology used herein is for the purpose of describing particular aspects only and is not intended to be limiting. As used herein, the singular forms "a," "an," and "the" are intended to include the plural, including "at least one," unless the context of the document clearly dictates otherwise. "Or" means "and / or." As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items. Furthermore, the terms "comprises" and / or "includes" or "comprises" and / or "comprising," as used herein, are understood to specify the presence of stated features, regions, integers, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, regions, integers, steps, operations, elements, components, and / or groups thereof. The term "or combinations thereof" refers to combinations including at least one of the above elements.
[0124] Spatially relative terms such as "below," "lower," "lower side," "upper," "above," and the like may be used herein for ease of description to describe the relationship of an element or feature to another element(s) or feature(s) as illustrated in the drawings. It will be understood that the spatially relative terms are intended to encompass different orientations of the device in use or operation in addition to the orientation illustrated in the drawings. For example, if the device in the drawings is turned over, elements described as "below" or "below" the other element or feature would now be oriented "above" the other element or feature. Thus, the exemplary term "below" can encompass both an orientation of above and below. The device may be oriented differently (rotated 90 degrees or at other orientations) and the spatially relative descriptors used herein interpreted accordingly.
[0125] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those of ordinary skill in the art to which this disclosure belongs. Furthermore, terms such as those defined in commonly used dictionaries should be interpreted to have a meaning that is not inconsistent with their meaning in the relevant art and in the context of this disclosure, and are not to be interpreted in an ideal or overly formal sense unless expressly defined herein.
[0126] Exemplary embodiments are described herein with reference to cross-sectional views that are schematic illustrations of idealized embodiments. Thus, variations from the shapes of the figures resulting, for example, from manufacturing techniques, are expected. Thus, the embodiments described herein should not be construed as limited to the particular shapes of regions illustrated herein, but should be construed to include deviations in shapes that result, for example, from manufacturing. For example, a region illustrated or described as flat may have uneven and / or non-linear features. Furthermore, sharp angles that are illustrated may be rounded. Thus, the regions illustrated in the drawings are schematic in nature, and their shapes are not intended to illustrate the exact shapes of the regions, and are not intended to limit the scope of the claims.
[0127] Although the present disclosure describes exemplary aspects, it will be understood by those skilled in the art that various modifications can be made and equivalents can be substituted for the elements of the disclosed aspects without departing from the scope of the disclosed aspects. In addition, many modifications can be made to adapt a particular situation or material to the teachings of the present disclosure without departing from its scope. Therefore, it is not intended that the disclosure be limited to the particular aspects disclosed as the best mode contemplated for carrying out the disclosure. It should also be understood that the aspects disclosed herein are to be considered in an illustrative sense only and not for the purpose of limitation. The description of features, advantages, or aspects of each embodiment should be considered as applicable to other similar features, advantages, or aspects of other embodiments.
[0128] Various modifications of the present disclosure in addition to those shown and described herein will be apparent to those skilled in the art and are intended to fall within the scope of the appended claims.
[0129] It is understood that all reagents and components are available from sources known in the art unless otherwise specified.
[0130] The patents, publications, and applications mentioned in this specification are indicative of the views of those skilled in the art to which the invention pertains, and are herein incorporated by reference to the same extent as if each individual patent, publication, or application was specifically and individually incorporated by reference.
[0131] The above description serves to illustrate certain embodiments of the present invention, but is not meant to be limiting in its practice. The following claims, including all equivalents, are intended to define the scope of the invention. [Aspect 1] 1. An electrochemical cell comprising: Formula Li 1+x MO 2+y A cathode comprising an electrochemically active polycrystalline cathode material comprising: In the formula, −0.9≦x≦0.3 and −0.3≦y≦0.3; M contains 80 atomic percent or more of Ni based on the whole of M; the electrochemically active cathode material comprises a non-uniform distribution of Co; A cathode; Li / Li + an anode comprising an electrochemically active material having an electrochemical redox potential of at least 400 mV at An electrochemical cell comprising: the cell is anode-controlled in volume, area, or both; Electrochemical cell. [Aspect 2] 2. The electrochemical cell of claim 1, the capacity ratio of the anode to the cathode is less than 1; or an area ratio of the anode to the cathode is less than or equal to 1; or Fulfilling both Electrochemical cell. [Aspect 3] 2. The electrochemical cell of claim 1, An electrochemical cell characterized by a nearly unchanged voltage / capacity profile following nail penetration with a blunt tipped 2 mm diameter stainless steel nail at a speed of 1 cm / sec. Aspect 4 2. The electrochemical cell of claim 1, Electrochemical cell characterized by nearly unchanged performance after 1000 cycles and subsequent storage for 33 months under 0V conditions. Aspect 5 2. The electrochemical cell of claim 1, An electrochemical cell characterized by less than 10% capacity fade at 10C after 1000 cycles at a charge rate of 10C and a discharge rate of 10C between 2.43V and 1.33V in a 45°C oven with no external constraints. Aspect 6 2. The electrochemical cell of claim 1, An electrochemical cell characterized by greater than 30% capacity delivery when discharged to 1.2V at a rate of 3.3C at -50°C. Aspect 7 2. The electrochemical cell of claim 1, An electrochemical cell that is chargeable at a rate of at least 1C at -50°C. Aspect 8 In the electrochemical cell according to any one of the first to eighth aspects, An electrochemical cell, wherein the anode, the cathode, or both, comprise a current collector substrate comprising aluminum. Aspect 9 In the electrochemical cell according to any one of the first to eighth aspects, The electrochemical cell, wherein the anode and the cathode are within a pouch cell. Aspect 10 In the electrochemical cell according to any one of the first to eighth aspects, An electrochemical cell, wherein the electrochemically active anode material comprises an oxide of Nb, an oxide of Sn, an oxide of Sb, an oxide of Ti, an oxide of Si, or an oxide of a combination of these elements. Aspect 11 11. The electrochemical cell of embodiment 10, An electrochemical cell wherein the electrochemically active anode material comprises an oxide of Nb. Aspect 12 11. The electrochemical cell of embodiment 10, An electrochemical cell, wherein the electrochemically active anode material comprises an oxide of Ti. Aspect 13 13. The electrochemical cell of embodiment 12, The oxide of Ti has the formula Li 4+a Ti 5 O 12+b It is expressed as In the formula, -0.3≦a≦3.3, -0.3≦b≦0.3. Electrochemical cell. Aspect 14 In the electrochemical cell according to any one of the first to eighth aspects, An electrochemical cell wherein the electrochemically active anode material has an electrochemical redox potential of 1 V or greater versus lithium metal. Aspect 15 In the electrochemical cell according to any one of the first to eighth aspects, the electrochemically active cathode material comprises a plurality of crystallites and grain boundaries between the plurality of crystallites; the concentration of cobalt, aluminum, or both at the grain boundaries is greater than the concentration at the centers of the adjacent crystallites; Electrochemical cell. Aspect 16 In the electrochemical cell according to any one of the first to eighth aspects, The formula Li 1+x MO 2+y wherein M comprises Ni and one or more metals selected from the group consisting of Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Cr, Fe, Mo, B, and any combination thereof. Aspect 17 In the electrochemical cell according to any one of the first to eighth aspects, 1. An electrochemical cell, wherein the electrochemically active cathode material comprises Ni and one or more of the elements Mg, Co, or Al. Aspect 18 1. An electrochemical cell comprising: Formula Li 1+x MO 2+y A cathode comprising an electrochemically active polycrystalline cathode material comprising: In the formula, −0.9≦x≦0.3 and −0.3≦y≦0.3; M contains 80 atomic percent or more of Ni based on the whole of M; the electrochemically active cathode material comprises a plurality of crystallites and grain boundaries between the plurality of crystallites; the concentration of cobalt, aluminum, or both at the grain boundaries is greater than the concentration at the centers of the adjacent crystallites; A cathode; Li / Li + two or more anodes comprising an electrochemically active anode material having an electrochemical redox potential of at least 400 mV at A porous polyolefin separator; an electrolyte comprising a lithium salt and a carbonate solvent; An electrochemical cell comprising: the anode and the cathode further comprise, independently, a binder mixed with the electrochemically active anode material and the electrochemically active cathode material; each of the anode and the cathode further independently comprises a current collector substrate comprising aluminum, the current collector of the cathode being coated on two sides with a respective electrochemically active material; the two or more anodes are terminal layers of an electrode stack; a capacity ratio of the anode to the cathode is less than 1; Electrochemical cell. Aspect 19 19. The electrochemical cell of embodiment 18, comprising: An electrochemical cell characterized by a nearly unchanged voltage / capacity profile following nail penetration with a blunt tipped 2 mm diameter stainless steel nail at a speed of 1 cm / sec. Aspect 20 19. The electrochemical cell of embodiment 18, comprising: An electrochemical cell characterized by nearly unchanged performance after 1000 cycles and subsequent storage for 33 months under 0V conditions. Aspect 21 19. The electrochemical cell of embodiment 18, comprising: An electrochemical cell characterized by having less than 10% capacity fade at 10C after 1000 cycles at a charge rate of 10C and a discharge rate of 10C between 2.43V and 1.33V in a 45°C oven when the electrochemical cell is in an unconstrained state. Aspect 22 19. The electrochemical cell of embodiment 18, comprising: An electrochemical cell characterized by delivering greater than 40% capacity when discharged to 1.2V at a rate of 3.3C at -50°C and charged at a rate of 1C at -50°C. Aspect 23 In the electrochemical cell according to any one of aspects 18 to 22, An electrochemical cell, wherein the electrochemically active anode material comprises an oxide of Nb, an oxide of Sn, an oxide of Sb, an oxide of Ti, an oxide of Si, or an oxide of a combination of these elements. Aspect 24 24. The electrochemical cell of claim 23, The oxide of Ti has the formula Li 4+a Ti 5 O 12+b It is expressed as In the formula, -0.3≦a≦3.3, -0.3≦b≦0.3. Electrochemical cell. Aspect 25 In the electrochemical cell according to any one of aspects 18 to 22, The formula Li 1+x MO 2+y wherein M comprises Ni and one or more metals selected from the group consisting of Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Cr, Fe, Mo, B, and any combination thereof. Aspect 26 In the electrochemical cell according to any one of aspects 18 to 22, 1. An electrochemical cell, wherein the electrochemically active cathode material comprises Ni and one or more of the elements Mg, Co, or Al.
Claims
1. 1. An electrochemical cell comprising: Formula Li 1+x M.O. 2+y A cathode comprising an electrochemically active polycrystalline cathode material comprising: In the formula, −0.9≦x≦0.3, −0.3≦y≦0.3, and M contains 80 atomic percent or more of Ni with respect to the whole of M; the electrochemically active cathode material comprises a non-uniform distribution of Co; A cathode; Li / Li + an anode comprising an electrochemically active material having an electrochemical redox potential of at least 400 mV at An electrochemical cell comprising: the cell is anode-controlled in volume, area, or both; Electrochemical cell.
2. 2. The electrochemical cell of claim 1 , a capacity ratio of the anode to the cathode is less than 1; Electrochemical cell.
3. 2. The electrochemical cell of claim 1 , An electrochemical cell characterized by an unchanged voltage / capacity profile following nail penetration with a blunt tipped 2 mm diameter stainless steel nail at a rate of 1 cm / sec.
4. 2. The electrochemical cell of claim 1 , Electrochemical cell characterized by unchanged performance after 1000 cycles and subsequent storage for 33 months under 0 V conditions.
5. 2. The electrochemical cell of claim 1 , An electrochemical cell characterized by less than 10% capacity fade at 10C after 1000 cycles at a charge rate of 10C and a discharge rate of 10C between 2.43V and 1.33V in a 45°C oven with no external constraints.
6. 2. The electrochemical cell of claim 1 , An electrochemical cell characterized by greater than 30% capacity delivery when discharged to 1.2V at a rate of 3.3C at -50°C.
7. 2. The electrochemical cell of claim 1 , An electrochemical cell that is chargeable at a rate of at least 1C at -50°C.
8. 8. The electrochemical cell according to claim 1 , An electrochemical cell, wherein the anode, the cathode, or both, comprise a current collector substrate comprising aluminum.
9. 9. The electrochemical cell according to claim 1 , The electrochemical cell, wherein the anode and the cathode are within a pouch cell.
10. 9. The electrochemical cell according to claim 1 , An electrochemical cell, wherein the electrochemically active anode material comprises an oxide of Nb, an oxide of Sn, an oxide of Sb, an oxide of Ti, an oxide of Si, or an oxide of a combination of these elements.
11. 11. The electrochemical cell of claim 10, An electrochemical cell wherein the electrochemically active anode material comprises an oxide of Nb.
12. 11. The electrochemical cell of claim 10, An electrochemical cell wherein the electrochemically active anode material comprises an oxide of Ti.
13. 13. The electrochemical cell of claim 12, The oxide of Ti has the formula Li 4+a Ti 5 O 12+b It is expressed as In the formula, −0.3≦a≦3.3 and −0.3≦b≦0.
3. Electrochemical cell.
14. 9. The electrochemical cell according to claim 1 , An electrochemical cell wherein the electrochemically active anode material has an electrochemical redox potential of 1 V or greater versus lithium metal.
15. 9. The electrochemical cell according to claim 1 , the electrochemically active cathode material comprises a plurality of crystallites and grain boundaries between the plurality of crystallites; the concentration of cobalt, aluminum, or both at the grain boundaries is greater than the concentration at the centers of the adjacent crystallites; Electrochemical cell.
16. 9. The electrochemical cell according to claim 1 , The formula Li 1+x M.O. 2+y wherein M comprises Ni and one or more metals selected from the group consisting of Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Cr, Fe, Mo, B, and any combination thereof.
17. 9. The electrochemical cell according to claim 1 , An electrochemical cell, wherein the electrochemically active cathode material comprises Ni and one or more of the elements Mg, Co, or Al.
18. 1. An electrochemical cell comprising: Formula Li 1+x M.O. 2+y A cathode comprising an electrochemically active polycrystalline cathode material comprising: In the formula, −0.9≦x≦0.3, −0.3≦y≦0.3, and M contains 80 atomic percent or more of Ni with respect to the whole of M; the electrochemically active cathode material comprises a plurality of crystallites and grain boundaries between the plurality of crystallites; the concentration of cobalt, aluminum, or both at the grain boundaries is greater than the concentration at the centers of the adjacent crystallites; A cathode; Li / Li + two or more anodes comprising an anode material comprising an electrochemically active material having an electrochemical redox potential of at least 400 mV at A porous polyolefin separator; an electrolyte comprising a lithium salt and a carbonate solvent; An electrochemical cell comprising: the anode and the cathode further comprise, independently, a binder mixed with the electrochemically active anode material and the electrochemically active cathode material; each of the anode and the cathode further independently comprises a current collector substrate comprising aluminum, the current collector of the cathode being coated on two sides with a respective electrochemically active material; the two or more anodes are terminal layers of an electrode stack; a capacity ratio of the anode to the cathode is less than 1; Electrochemical cell.
19. 20. The electrochemical cell of claim 18, An electrochemical cell characterized by an unchanged voltage / capacity profile following nail penetration with a blunt tipped 2 mm diameter stainless steel nail at a rate of 1 cm / sec.
20. 20. The electrochemical cell of claim 18, Electrochemical cells characterized by unchanged performance after 1000 cycles and subsequent storage under 0 V conditions for 33 months.
21. 20. The electrochemical cell of claim 18, an electrochemical cell characterized by a capacity fade at 10C of less than 10% after cycling 1000 times at a charge rate of 10C and a discharge rate of 10C between 2.43V and 1.33V in a 45°C oven when the electrochemical cell is in an unconstrained state.
22. 20. The electrochemical cell of claim 18, An electrochemical cell characterized by delivering greater than 40% capacity when discharged to 1.2V at a rate of 3.3C at -50°C and charged at a rate of 1C at -50°C.
23. 23. The electrochemical cell according to claim 18, An electrochemical cell, wherein the electrochemically active anode material comprises an oxide of Nb, an oxide of Sn, an oxide of Sb, an oxide of Ti, an oxide of Si, or an oxide of a combination of these elements.
24. 24. The electrochemical cell of claim 23, The oxide of Ti has the formula Li 4+a Ti 5 O 12+b It is expressed as In the formula, −0.3≦a≦3.3 and −0.3≦b≦0.
3. Electrochemical cell.
25. 23. The electrochemical cell according to claim 18, The formula Li 1+x M.O. 2+y wherein M comprises Ni and one or more metals selected from the group consisting of Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Cr, Fe, Mo, B, and any combination thereof.
26. 23. The electrochemical cell according to claim 18, An electrochemical cell, wherein the electrochemically active cathode material comprises Ni and one or more of the elements Mg, Co, or Al.
Citation Information
Patent Citations
All solid lithium ion secondary battery and solid electrolyte
JP2006185913A
Lithium-ion secondary battery
JP2012014968A
Polycrystalline metal oxide, method for producing the same, and product containing the same
JP2014528891A
Method for manufacturing nonaqueous electrolyte secondary battery
JP2015015087A
Nonaqueous electrolyte battery, method of manufacturing nonaqueous electrolyte battery, and battery pack
JP2016035901A